PTU-125 Biochemical Patterns Of Presentation In Primary Sclerosing Cholangitis: Younger Age At Onset Is Associated With A Lower Alp/ast Ratio. (9th June 2014) - Trivedi, PJ; Robinson, J; Wright, T; Bruns, T; Li, K-K; Shah, H; Adams, D; Ferguson, J; Hirschfield, G
Abstract : Introduction: Autoimmune sclerosing cholangitis is the paediatric term applied to children presenting with features of autoimmune hepatitis and sclerosing cholangitis. We hypothesised that if this inflammatory phenotype was a continuum, young adults with primary sclerosing cholangitis (PSC) would also have a more inflammatory presentation. Methods: We undertook a retrospective case-note review of our patients with an established diagnosis of PSC presenting between 2003–2013 (n = 116). Clinical characteristics and laboratory parameters were collected, and differences in disease phenotype correlated with age at presentation (SPSSv21). Results: The median age of disease presentation in our cohort was 44 years (IQR:25–56). Although there was no significant correlation between patient age and mode of disease presentation, younger age was more commonly associated with lower baseline serum ALP (Spearman's rho = 0.239; P = 0.011). Patient age negatively correlated with ALP:AST ratio ( rho = 0.252; P = 0.008); however, there was no correlation with serum AST, bilirubin, albumin, platelet count, INR, IgG titre or ANA/ASMA status. Using quartile cut-points in order to compare extremes of age, individuals presenting below the age of 25 (Q4; 7.6; 3.2–13.0) ( P = 0.023). Age <25 at disease presentation was more often associated with an ALP:AST ratio <1.5 (11/25 [44%] vs. 4/25; [16%], P = 0.017). There were no significant differences in IBD phenotype, number of patients meeting transplantation or median time to transplant. Conclusion: Younger patients more commonly have a lower ALP/AST ratio at disease presentation, and may indicate a more 'inflammatory' PSC phenotype. Disclosure of Interest: None Declared.